DYRK1A modulates fear memory formation via epigenetic modification - Dae-Si Kang; Ja Wook Koo (Molecular Brain)
Abstract Fear memory formation is crucial for survival, with the hippocampus playing a central role. This study investigates the behavioral and molecular aspects of fear memory formation, focusing on Dual-specificity tyrosine phosphorylation-regulated kinase 1 A (DYRK1A), a protein known to be critical for cognitive functions. Our results demonstrate that DYRK1A expression in hippocampal CA1 pyramidal neurons is downregulated after contextual fear conditioning (CFC). We also observed a decrease in DYRK1A binding to the Maoa promoter, suggesting its involvement in transcriptional regulation during fear memory formation. In subsequent experiments, we modulated DYRK1A expression using viral vectors. DYRK1A overexpression reduced freezing behavior, while knockdown enhanced it. At the molecular level, DYRK1A overexpression resulted in elevated H3K4me3 levels, while knockdown decreased it. These findings indicate that DYRK1A regulates fear memory formation via epigenetic modifications, altering H3K4me3 levels and influencing Maoa transcription in the hippocampus. This research highlights the nuclear role of DYRK1A and suggests its potential as a therapeutic target for neuropsychiatric disorders related to fear and memory.